Multi-step reflux extraction of bio-pharmaceutical phenolic bioactives from balsam apple (Momordica balsamina L.). Issue 1 (1st January 2020) - Olalere, Olusegun Abayomi; Gan, Chee Yuen
Abstract : In this study, the impacts of parameter combinations on the response (total phenolic yield) were evaluated using the single experiments and two-level factorial design. The investigated parameters with their value range include; the microwave extraction time (1–5 min), power level (400–600 W), temperature (60–80°C), the solvent-feed ratio, SFR (8–12 mL/g) and solvent concentration (50–80%). The result of this investigation succinctly presented the solvent concentration as the highest contributing parameters, far above the Bonferroni limit (8.37517) and t -value limit (3.18245). However, the temperature, SFR and microwave duration provided insignificant contribution to the response settings. The result of the spectrometry chromatographic analysis identified 22 phenolics compounds from the extracts which invariably revealed their potential biological functions. The study therefore adequately elucidated the contributing factor in the microwave recovery of total phenolic constituents from the M. balsamina leaves with potential use as scale-up parameters in drug applications.